ASSESSING DAILY INTAKE OF INDOOR AIR POLLUTANTS FROM 3D PRINTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The scientific community is increasingly focusing on indoor air quality (IAQ) more than ever, driven by on-going research and fresh perspectives including development of 3D technologies. Exposure dose (EDa) resulting from inhalation of indoor air pollutants emitted by 3D printers were calculated in this study. The consideration of emissions from 3D printers is based on experimental data, primarily sourced from reviewed literature. However, this research also includes some experimental values, excluding the background levels of these pollutants. Experiments were conducted using several 3D printers available (Zortrax M300 Dual) to compare the indoor air pollutants generated and their concentrations with information gathered from earlier research. In the experiments, filaments containing ABS (acrylonitrile, butadiene, and styrene copolymer material, commonly used for 3D printing) were utilized. EDa values of styrene, toluene, formaldehyde, and acetaldehyde for 8-hour and 12-hour shifts for average and maximal (reported) concentrations were calculated based on the available experimental and literature data. The average concentrations of these pollutants were determined by calculating the arithmetic mean, which incorporated concentration values obtained from previous research and experimental data collected within this study. It was concluded that further investigation should focus on aerial concentrations of styrene generated during 3D printing. Calculated EDa for styrene from several studies exceeded the recommended guidelines for Tolerable Daily Intake (TDI) set by the World Health Organization (WHO) by at least 35%. Further exploration is imperative to incorporate additional pathways of indoor air pollutant exposure, such as skin contact and ingestion.  This comprehensive approach will provide a more thorough understanding of the overall health risks associated with indoor air quality during 3D printing.